2010
DOI: 10.1186/1743-7075-7-62
|View full text |Cite
|
Sign up to set email alerts
|

The effect of calcium and vitamin D supplementation on obesity in postmenopausal women: secondary analysis for a large-scale, placebo controlled, double-blind, 4-year longitudinal clinical trial

Abstract: BackgroundIt is undetermined whether calcium supplementation has an effect on obesity or body composition in postmenopausal women. The purpose of the study is to detect the effect of calcium supplementation on indices of obesity and body composition.MethodsThis is a secondary analysis of data from a population-based, double-blind, placebo-controlled, randomized trial designed to determine the effects of calcium and vitamin D on osteoporotic fractures. The cohort included 1179 postmenopausal women who were rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
43
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 40 publications
0
43
2
Order By: Relevance
“…Other studies, although not weight-loss studies, also found weak relationships between changes in fat mass and 25OHD levels. 12,17 It appears that most studies either observed an increase in 25OHD levels, a pattern where there were greater increases in those that lost more weight or a relationship between the degree of weight loss and increases in 25OHD levels. It may be possible that a threshold of weight loss is needed to see an increase in 25OHD levels.…”
Section: Do 25-hydroxyvitamin D Levels Change With Weight Loss?mentioning
confidence: 99%
See 3 more Smart Citations
“…Other studies, although not weight-loss studies, also found weak relationships between changes in fat mass and 25OHD levels. 12,17 It appears that most studies either observed an increase in 25OHD levels, a pattern where there were greater increases in those that lost more weight or a relationship between the degree of weight loss and increases in 25OHD levels. It may be possible that a threshold of weight loss is needed to see an increase in 25OHD levels.…”
Section: Do 25-hydroxyvitamin D Levels Change With Weight Loss?mentioning
confidence: 99%
“…After 4 years, weight decreased in the vitamin D and calcium group, was unchanged in calcium group, and increased in placebo (values not reported). 12 When looking at body composition, there was a gain in trunk fat mass and a loss of trunk lean mass, and this was greatest in the placebo group and similar in both supplemented groups. 12 This suggested vitamin D had no added benefit; however, the changes in 25OHD levels were related to changes in body mass index (BMI) and trunk fat mass (r=-0.15; p<0.01), and only those taking vitamin D and calcium supplementation had significant increases in 25OHD levels (~40 % increase) while the others remained stable.…”
mentioning
confidence: 97%
See 2 more Smart Citations
“…5 Vitamin D deficiency can cause various other health problems since its deficiency often associated with obesity. 6 Its deficiency may also alter insulin synthesis since glycemia is improved with replenishment of vitamin D in type 2 diabetic patients hence proving its significance in diabetes mellitus. 7 Moreover vitamin D deficiency may also be cause of atherosclerosis since vitamin D supplement have some beneficial effect on elastic properties of artery wall of post-menopausal women.…”
Section: Introductionmentioning
confidence: 99%